Multiplier Effect Analysis of Tulung Ni Lenggo Lake Management as Sustainable Ecotourism - Irma Yuliana; Heru Susilo; Irman Irawan; Fitriyana Fitriyana (Faculty of Marine and Fisheries, Universitas Syiah Kuala, 2025)
Tulung Ni Lenggo is a lake area in Berau Regency that has been opened as an ecotourism location since 2016. The manager chose the ecotourism concept as an effort to implement the concept of sustainable development. This study aimed to analyze the direct, indirect and advanced economic impacts and multiplier effects of ecotourism of Tulung Ni Lenggo Lake in Berau Regency. The analysis method used was the multiplier effect economic impact analysis method. The direct economic impact on the business unit was IDR 273,043,166.67/year, the indirect economic impact was IDR 369,096,833.33/year and the further economic impact was IDR 173,880,000.00/year. The value of the Keynesian multiplier effect was 0.07, the value of income multiplier ratio type 1 was 2.35, and the value of income multiplier ratio type 2 was 2.99. This means that the management of Lake Tulung Ni Lenggo as sustainable ecotourism had been able to provide an economic impact on business unit income and labor in the ecotourism area, which also impacts increasing consumption and the local economy.Keywords:Economic effectTulung Ni LenggoLakeBerau Regency